The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10875-011-9512-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Pharmacokinetics of a 10% Liquid Immune Globulin Preparation (GAMMAGARD LIQUID, 10%) Administered Subcutaneously in Subjects with Primary Immunodeficiency Disease

Abstract: A multi-center, prospective, open-label study was conducted in primary immunodeficiency disease patients to determine the tolerability and pharmacokinetics of a 10% liquid IgG preparation administered subcutaneously. Forty-nine subjects (3-77 years old) were enrolled. Pharmacokinetic equivalence of subcutaneous treatment was achieved at a median dose of 137% of the intravenous dose, with a mean trough IgG level of 1,202 mg/dL at the end of the assessment period. The overall infection rate during subcutaneous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
76
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 22 publications
16
76
1
2
Order By: Relevance
“…In summary, SCIG clinical trials have shown relatively high IgG trough levels when compared with IVIG in the same study (Wasserman , 2011.…”
Section: Subcutaneous Immunoglobulin Therapymentioning
confidence: 66%
See 1 more Smart Citation
“…In summary, SCIG clinical trials have shown relatively high IgG trough levels when compared with IVIG in the same study (Wasserman , 2011.…”
Section: Subcutaneous Immunoglobulin Therapymentioning
confidence: 66%
“…Subcutaneous administration of Gammagard Liquid was also studied in an open-label trial of 49 patients with PID (Wasserman et al 2011). All subjects received IV infusions of Gammagard Liquid for 13 weeks.…”
Section: Subcutaneous Immunoglobulin Therapymentioning
confidence: 99%
“…In this study, 87 adults and children 4-78 years of age with PIDD received IVIG every 3 or 4 weeks for 3 months, and 83 patients were then treated with IGHy for approximately 14-18 months. Of the 83 patients, 31 received 3 months of IVIG followed by 12 months of conventional SCIG without rHuPH20 in a previous study (NCT00546871) [38] and then were enrolled to receive IGHy for 14-18 months in the Phase III study [16]. All patients received IGHy at the same dose and frequency as their prestudy IVIG.…”
Section: Phase III and Extension Studies Study Design And Patientsmentioning
confidence: 99%
“…Adjusting the dose to achieve the same AUC is considered necessary because of presumed differences in the bioavailability of IgG and similar proteins when given by the intramuscular (IM) or subcutaneous (SC) routes as compared with the intravenous (IV) route [2]. Dose adjustments of 120 % to 153 % have been used in different studies of polyclonal SCIG, implying that the different products have different bioavailabilities [3][4][5][6]. However, "non-inferiority" designs, which accept a margin of ±20 % of AUC, have been employed, so the derived dose adjustments may not reflect the actual bioavailability of different products [1].…”
Section: Introductionmentioning
confidence: 99%